A study of overloading problems on truck trailer operations at United Seino Transportation (M) Sdn Bhd / Khairul Anuar Abu Osman - Abu Osman, Khairul Anuar (1993)
Overloading activity on Malaysian roads is a common phenomenon done by the irresponsible overland freight transport operator. UST is one of the irresponsinble road freight transport operator that practice illegal overloading activity. The objective of this study is to identify the problems caused by overloading and also to make recommendations and provide solutions to the overloading problems. This can be achieved by conducting a survey on various relevant places, attending seminars, participating in trucking activities, interviews and also distributing questionaires to the drivers. Findings show that overloading activities is not the best solutions to increase the company revenue in a long run. In addition, the overloading activity increase the total cost of operation through the increase in tyre and fuel cost as well as wear and tear to the truck trailer itself. Overloading also can compromise the safety aspects of the vehicles, drivers and also pose danger to public.